(untitled) (Education in the 21st Century, 2023)
Out-of-hospital cardiac arrest is a leading cause of premature death worldwide. High-quality cardiopulmonary resuscitation (CPR) is a means to improve cardiac survival rate and achieve optimal patient outcomes. Chest compression-only cardiopulmonary resuscitation (CO-CPR) has emerged as an alternative to standard CPR (S-CPR), using both chest compressions and rescue breaths. Since 2010, CPR guidelines recommend CO-CPR for both untrained bystanders and trained bystanders unwilling to perform rescue breaths. CO-CPR is easier to teach, easier to perform and may be associated with increased CPR rates, and thereby with a higher rate of overall survival. The reasons for the adoption of CPR new strategy in out of hospital cardiac arrest could also include focus on minimizing interruptions in chest compressions. The goal of saving more lives relies not only on type of effective CPR and solid quality science but also the effective education of lay people and healthcare professionals. This article provides some basis of a successful educational strategy for improved CPR education, taking into consideration new recommendations of European Resuscitation Council and American Heart Association (ERC Guideline 2015, AHA Guideline 2015). There is increased emphasis on the rapid identification of potential cardiac arrest by dispatchers, with immediate provision of CPR instructions to the caller. CPR should be performed immediately on any person who has become unconscious and is found not breathing normally or with absent breathing. The sequence of basic CPR training was suggested. The study might improve awareness of basic CPR new strategy, support CO-CPR as an option in future resuscitation course developments.